METODE DOUBLE EKSPONENSIAL SMOOTHING DALAM MEMPERKIRAKAN JUMLAH KEBUTUHAN ENERGI LISTRIK DI PT PLN (PERSERO) WILAYAH SUMUT - Herion Tarigan; Pardomuan Sitompul (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Electrical energy is one of the most important things in human life. Electrical energy is needed in the industrial sector. In meeting the needs of electrical energy, good planning is needed by predicting the needs of electrical energy. Holt's Double Exponential Smoothing method is a method that can be used to predict electrical energy needs. The results of forecasting the demand for electrical energy at PT PLN (Persero) for the North Sumatra Region for 2022 to 2030 use the Double Double Exponential Smoothing method from Holt (with a value of α = 0.99 and γ = 0.1 which has a MAPE value of 2.0372%. ) namely 13933.19 gwh, 14478.46 gwh, 15023.73 gwh, 15569.00 gwh, 16114.26 gwh, 16659.53 gwh, 17204.80 gwh, 17750.06 gwh, 18295.33 gwh.